Aturan-Aturan untuk Taat dalam Konteks Penyembahan Kepada Allah : Menurut Ulangan 16:21-22;17:1 - Nobel A. Tampubolon; Paulina Silitonga (Jurnal Pendidikan Agama dan Teologi, 2024)
This journal investigates the rules established to guide obedience in the context of worshiping God, as outlined in Deuteronomy chapters 16:21-22 and 17:1. Through the analysis of these texts, the study aims to understand the role of these rules in shaping the worship of God. The research method involves exploring the historical and religious context in which the rules were revealed. The results of the study highlight the significance of these rules in directing the principles of right worship and deepening spiritual obedience. The practical implications of the findings can provide valuable insights for religious communities seeking to understand and apply moral principles in the context of the worship of God.